Neoadjuvant treatment in locally advanced thyroid cancer: a single institution experience - Xu, Ling-Feng; Shi, Nuo; Niu, Jia-Liang; An, Ning; Xi, Yi-Qing; Huang, Qiu-Yi; Jiang, Liang; Chen, Jian (Frontiers in Oncology, 2025)
BackgroundLocally advanced thyroid cancer is a kind of aggressive malignancy with poor overall survival (OS). Neoadjuvant therapy has shown a certain efficacy in locally advanced thyroid cancer. The objective of this study was to assess the efficacy and feasibility of surgery following neoadjuvant therapy in patients.MethodsIn a retrospective study, we analyzed sixteen patients with locally advanced thyroid cancer from January 2019 to June 2024 in our institution. Among them, 7 patients with unresectable differentiated thyroid cancer (DTC) received tyrosine kinase inhibitors (TKI), and 2 patients with poorly differentiated thyroid cancer (PDTC) and 7 patients with anaplastic thyroid carcinoma (ATC) received a combination therapy of TKI, immune checkpoint inhibitors (ICI) or chemotherapy. Response and progression were evaluated by the Response Evaluation Criteria in Solid Tumors (RECIST 1.1). OS was calculated using the Kaplan-Meier method.Results16 (4 male and 12 female) patients with locally advanced thyroid cancer were enrolled in this study, in which 10 patients (62.5%) accepted surgery following neoadjuvant therapy and 6 patients (37.5%) refused surgery. The objective response rate (ORR) was 50.00%, and disease control rate (DCR) was 81.25%. Two partial response (PR), two stable disease (SD) and one progressive disease (PD) patients achieved R0/1 resections after neoadjuvant treatment, resulting in a R0/1 resection rate of 50.00%. Grade III/IV toxicities developed in 2 of 16 patients, requiring dose reduction/discontinuation of TKI. The median OS was 17 months, with one PDTC, four ATC and six DTC patients still alive without relapse.ConclusionsNeoadjuvant treatment, including TKI, ICI or chemotherapy treatment, was safe and effective in locally advanced thyroid cancers and could create radical surgery opportunities to improve the prognosis of patients.